Efficacy and safety of Ho:YAG Laser Lithotripsy for ureteroscopic removal of proximal and distal ureteral calculi - Khoder, Wael Y (BioMed Central, 2014)
BACKGROUND: Laser lithotripsy is an established endourological modality. Ho:YAG laser have broadened the indications for ureteroscopic stone managements to include larger stone sizes throughout the whole upper urinary tract. Aim of current work is to assess efficacy and safety of Ho:YAG laser lithotripsy during retrograde ureteroscopic management of ureteral calculi in different locations. METHODS: 88 patients were treated with ureteroscopic Ho:YAG laser lithotripsy in our institute. Study endpoint was the number of treatments until the patient was stone-free. Patients were classified according to the location of their stones as Group I (distal ureteric stones, 51 patients) and group II (proximal ureteral stones, 37). Group I patients have larger stones as Group II (10.70 mm vs. 8.24 mm, respectively, P = 0.020). RESULTS: Overall stone free rate for both groups was 95.8%. The mean number of procedures for proximal calculi was 1.1 ± 0.1 (1–3) and for distal calculi was 1.0 ± 0.0. The initial treatment was more successful in patients with distal ureteral calculi (100% vs. 82.40%, respectively, P = 0.008). No significant difference in the stone free rate was noticed after the second laser procedure for stones smaller versus larger than 10 mm (100% versus 94.1%, P = 0.13). Overall complication rate was 7.9% (Clavien II und IIIb). Overall and grade-adjusted complication rates were not dependant on the stone location. No laser induced complications were noticed. CONCLUSIONS: The use of the Ho:YAG laser appears to be an adequate tool to disintegrate ureteral calculi independent of primary location. Combination of the semirigid and flexible ureteroscopes as well as the appropriate endourologic tools could likely improve the stone clearance rates for proximal calculi regardless of stone-size.